Kewarisan Bilateral Masyarakat Muslim Jawa: Studi Komparasi Pandangan Hazairin dan Fakta Empiris - al Anam, Muhammad Mufti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This research aims to describe the practice of bilateral inheritance among religious figures in Satreyan Village, Kanigoro Blitar District, then compare it with Hazairin's theory of bilateral inheritance to find out whether there are similarities in the legal explanation. This research is empirical juridical research using a comparative approach. The research results show that although both have the same spirit in efforts to accommodate equal inheritance rights for women and men, there are differences in legal reasoning. Bilateral inheritance among Satreyan religious figures was agreed upon in the heirs forum as an effort to sad dzariah without ignoring faraid. Meanwhile, Hazairin, in his bilateral inheritance, carried out new legal istinbath on inheritance verses and hadiths with different legal reasoning from the classical fuqaha'.